Trait Appreciation of Beauty: A Story of Love, Transcendence, and Inquiry. Issue 4 (December 2018) - Diessner, Rhett; Pohling, Rico; Stacy, Shawnee; Güsewell, Angelika
This review of the trait of appreciation of beauty (AoB) draws from the literature in personality psychology, philosophy, religion, neuroscience, neuro-aesthetics, evolutionary psychology, and the psychology of morality. We demonstrate that AoB can be mapped onto a definition of appreciation that includes perceptual, cognitive, emotional, trait, virtue, and valuing elements. A classic component of defining beauty, unity-in-diversity, is described based on the works of a variety of major philosophers. We next describe that there are at least four channels of appreciation of beauty: natural beauty, artistic beauty, moral beauty, and beautiful ideas. Examining the neuro-aesthetics research indicates that many networks of the brain are involved in mental acts of appreciating beauty, but the medial orbital front cortex (mOFC) is implicated across all four channels of beauty. We then explain how the trait of AoB is a member of three different families of traits: traits of love, traits of transcendence, and traits of inquiry. Next we briefly explain why Kant may have been more correct than Hegel concerning beauty and the good soul. We then present evidence that women may appreciate beauty somewhat more than men. Data from many cultures and nations consistently indicate this. After that we claim AoB leads to individual and collective flourishing. We examine and summarize studies that indicate appreciation of natural beauty leads to a wide variety of positive outcomes; we focus on the importance of open-mindedness that accompanies engagement with artistic beauty; and we summarize studies regarding the moral emotion of elevation and appreciation of moral beauty. Suggested future directions for research are embedded in each subsection of the paper.